2008
DOI: 10.1038/jid.2008.140
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: IL-12 Deficiency Exacerbates Inflammatory Responses in UV-Irradiated Skin and Skin Tumors

Abstract: IL-12 deficiency has been shown to promote photocarcinogenesis in mice. As UVB-induced inflammation is an important tumor-promoting event in the development of skin tumors, we determined the effects of IL-12-deficiency on UVB-induced inflammatory responses in mice. For this purpose, IL-12-knockout (IL-12 KO) and their wild-type counterparts were subjected to a photocarcinogenesis protocol; skin and tumor samples were collected at the termination of the experiment, and analyzed for biomarkers of inflammation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 34 publications
2
53
1
1
Order By: Relevance
“…Using wild-type (C3H/HeN) and IL-12-knockout mice Meeran et al demonstrated that IL-12-deficiency significantly enhanced levels of pro-inflammatory cytokines (IL-1 β, TNF-α and IL-6) and COX-2 as well as leukocyte infiltration (MPO activity) following UV treatment (80% UVB; 180 mJ/cm 2 ) (ref. 32 ). As shown in Table 1, under our conditions UVB treatment had no significant effect on IL-12(p40) plasma expression.…”
Section: Discussionmentioning
confidence: 99%
“…Using wild-type (C3H/HeN) and IL-12-knockout mice Meeran et al demonstrated that IL-12-deficiency significantly enhanced levels of pro-inflammatory cytokines (IL-1 β, TNF-α and IL-6) and COX-2 as well as leukocyte infiltration (MPO activity) following UV treatment (80% UVB; 180 mJ/cm 2 ) (ref. 32 ). As shown in Table 1, under our conditions UVB treatment had no significant effect on IL-12(p40) plasma expression.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced expression of COX-2 in skin exposed to UV radiation has been identified as a risk factor for the development of skin cancer. (5,6) Cyclooxygenase-2 generates prostaglandins that are thought to play a central role in orchestrating the events involved in cancer invasion and metastasis. Prostaglandin E 2 (PGE 2 ) exerts its effects through G-protein coupled receptors (EP1, EP2, EP3, and EP4) and has been implicated in angiogenesis, invasion, and metastasis.…”
mentioning
confidence: 99%
“…1 UVBinduced skin inflammatory reactions constitute a potent tumor-promoting event that contributes to photocarcinogenesis. [14][15][16] Thus, development of a method for regulating UVB-induced acute effects is important for protection against photocarcinogenesis. However, the molecular mechanisms by which UVB induces acute effects on the skin have not been fully clarified.…”
mentioning
confidence: 99%